COGNITIVE-BEHAVIOR MODIFICATION: KEMANJURAN TEKNIK SELF-INSTRUCTION SEBAGAI MEDIA UNTUK MENINGKATKAN MOTIVASI BERPRESTASI SISWA SMAN 03 KOTA BENGKULU - Utomo, Prio; Prayogi, Fiki (Jurnal Inspirasi Bimbingan dan Konseling (JGCI), 2020)
This research is motivated by the phenomenon of the problem that shows the low achievement motivation of students at school. The purpose of this study was to examine the effectiveness of using self-instruction techniques as a medium to increase student achievement motivation. The research design used a pre-experimental design, the research method used one group pretest and a posttest design. The research subjects were students of class XI SMA 03 Bengkulu City in 2019 with a total of 10 students, the subjects were selected using a purposive sampling technique. The research instrument uses; (1) treatment materials, (2) achievement motivation scale, and (3) observation guidelines. Data analysis used nonparametric analysis with Wilcoxon Signed Rank Test statistical test. The results of hypothesis testing show that H0 is rejected and H1 is accepted, this means that there is an increase in student achievement motivation after being given self-instruction techniques. The conclusion of the research shows that the self-instruction technique is effective and can be used as a medium to increase students' achievement motivation.